Clearing the Path for Developing Learners: Essential Literacy Skills to Support Achievement in Every Content Area - Grafwallner, Peg (Solution Tree, 2023)
All learning is based on the mastery of essential literary skills, and in this impactful title from author and reading specialist Peg Grafwallner, educators will discover tools they need to embed literacy into all subjects. Using this book's skill-building strategies and reproducibles, educators can effectively teach those literacy skills to support developing students as they learn to read, write, and think critically. Through this title, educators will discover how to: (1) expand their teaching methods to include literacy skills; (2) introduce literacy into daily lesson planning; (3) embed reading comprehension into any subject area; (4) create a positive classroom culture through relevant and relatable vocabulary strategies; and (5) scaffold instruction using literacy strategies to boost subject-area comprehension.